Anomalous Interfacial Electronic Structure of Solid Films of Non‐Planar π‐Conjugated Molecule 6‐Cycloparaphenylene. Issue 16 (10th April 2022) - Furuichi, Takaya; Inoue, Takuya; Miyaji, Kouki; Kanai, Kaname
Abstract: n ‐Cycloparaphenylene ([ n ]CPP) is a non‐planar π‐conjugated molecule with a macrocyclic, hoop‐like molecular structure that allows for control of the electronic structure unlike planar molecules. Thus, [ n ]CPP has the potential as a novel functional material in organic electronics. In this study, the unique electronic structure of [6]CPP is revealed, which originates from its macrocyclic molecular structure by comparison with p ‐sexiphenyl, a linear molecule also consisting of six phenylenes. The morphology of the vapor‐deposited [6]CPP polycrystalline film is found to be highly dependent on the evaporation rate and the type of substrate. It is also found that a [6]CPP molecular layer is formed at the interface between the film and gold substrate, which has a much smaller energy gap than that of the bulk [6]CPP. This anomalous molecular layer is composed of [6]CPP molecules with a smaller dihedral angle than that in the bulk because of the interaction with a gold substrate. When [6]CPP is used as a semiconducting layer in electronic devices, this layer can play a role in improving the charge injection efficiency from the electrode to the [6]CPP film. Abstract : In solid thin films of the non‐planar π‐conjugated molecule 6‐cycloparaphenilene ([6]CPP), deformation of the molecular structure at the metal substrate surface results in a reduced energy gap at the substrate interface. This unusual interface state originates from the distinctive macrocyclic and electronic structure of [6]CPP.